Could platelet activating factor play a role in developmental dyslexia? - Taylor, K; Richardson, A; Stein, J (2001)
Post-mortem studies by Galaburda and colleagues on the brains of developmental dyslexics found characteristic neuronal abnormalities: ectopias, microgyria, and fewer large-soma cells in sensory thalamus. An association between dyslexia and immune dysfunction has also been proposed. We describe a mechanism which may explain these observations. Platelet-activating factor (PAF) is a pro-inflammatory lipid implicated in neurological disorders. We propose that PAF may also be involved in dyslexia.